MICROBIAL DEGRADATION OF CORRINOIDS III. : Pigments Derived From Vitamin B(12) By Pseudomonas Rubescens - Burgus, R. C. (1964)
Burgus, R. C. (Wayne State University, Detroit, Mich.), J. B. Hufham, W. M. Scott, and J. J. Pfiffner. Microbial degradation of corrinoids. III. Pigments derived from vitamin B(12) by Pseudomonas rubescens. J. Bacteriol. 88:1139–1144. 1964.—Products derived from vitamin B(12) by Pseudomonas rubescens under anaerobic conditions were examined. After incubation of the organism in broth containing Co(57)- or P(32)- vitamin B(12), electrophoresis of the extracted corrinoids yielded two major, yellow, radioactive fractions, designated A and B, with spectral and electrophoretic properties similar to pigments I and II, derived from vitamin B(12) by Aerobacter aerogenes. Fractions A and B were essentially inactive in promoting the growth of Lactobacillus leichmannii. Chromatography on carboxymethylcellulose separated both fractions A and B into four yellow, radioactive fractions. The absorption spectrum of each of the major subfractions showed a maximum in the ultraviolet region characteristic of a 5,6-dimethylbenzimidazole nucleotide, but lacked a maximum in the 360-mμ region characteristic of vitamin B(12) and many of its analogues and derivatives. The pigments were stable to cyanide and, although they were more stable to air and light than were the vitamin B(12) coenzymes and coenzyme analogues, they were apparently slowly decomposed by light. The data suggest that the bacteria alter the corrin nucleus of vitamin B(12).